Komparasi Islamicity Performance Index Sebelum dan Selama Pandemi Covid-19 Serta Dampak Faktor Makroekonomi Pada Bank Umum Syariah di Indonesia - Muhamad Umar Mai; Setiawan Setiawan; Nurhadi Kamaluddin; Nahlarriva Zackia (Journal of Applied Islamic Economics and Finance, 2022)
The Covid-19 pandemic that took place in Indonesia has affected all sectors of life, especially the economic sector. The impact on macroeconomic conditions can be seen from the decline in inflation rates, Gross Domestic Product (GDP), and interest rates as well as rising unemployment rates. The purpose of this study was to compare the Islamicity Performance Index of Islamic Commercial Banks (BUS) before and during Covid-19 and to determine the magnitude of the influence of macroeconomic conditions on the Islamicity Performance Index. This research is a quantitative research with secondary data, the number of samples is 10 BUS selected using purposive sampling method. The research methods used include paired sample t-test and panel data regression analysis. The results of this study indicate that together the independent variables have an effect on the Islamicity Performance Index. Partially, the variables of GDP and unemployment have a negative and significant effect on the Islamicity Performance Index. While the inflation variable and the BI Rate have no significant effect on the Islamicity Performance Index